Development of an analysis of swimming techniques using instrumentation and the development of a new measurement method at Brno University of Technology, Centre of Sports Activities - Bátorová, M.; Stastný, J.; Motycka, J.; Janura, M. (Journal of Human Sport & Exercise, 2016)
This article provides an overview of the development of measuring methods and instrumentation for the analysis of swimming techniques around the world, and describes in more detail the Tachograph method used in BUT (Brno University of Technology), including information about the currently developed method for measuring the swimmers using accelerometers. Our aim is to present a comprehensive view of the issue and describe the direction of the current development of measurement techniques used in swimming. The article further describes in detail the physical nature of the measurement methods and discusses their pros and cons. In addition to conventional methods (speedometer, accelerometer), we also mention unconventional methods (CFD method, 3D motion analysis etc.). The main contribution of the paper is in highlighting new directions and methods of measurement in swimming, including a specific approach for the evaluation of swimming techniques at the Brno University of Technology (BUT), where the scientific team at the Center of Sports Activities (CESA) has for several years developed and refined a tachograph measuring method with synchronous underwater video recording of swimmers. This method was used with swimmers from the Czech national swimming team and from Czech sports secondary schools as part of ongoing research and efforts towards more accurate measurements. Finally, the article describes current developments in measuring methods done at BUT using accelerometers.